Governance and Private Investment in the Middle East and North Africa - Aysan, Ahmet Faruk; Nabli, Mustapha Kamel; Véganzonès-Varoudakis, Marie-Ange (World Bank, Washington, DC, 2012)
This paper addresses the issue of the low level of private investment in the Middle East and North Africa (MENA) region, with special emphasis on the role of governance. Based on the existing literature, the authors categorize what types of governance institutions are more detrimental to entrepreneurial investments. They then estimate a simultaneous model of private investment and governance quality where economic policies concurrently explain both variables. The empirical results show that governance plays a significant role in private investment decisions. This result is particularly true in the case of "administrative quality" in the form of control of corruption, bureaucratic quality, investment-friendly profile of administration, and law and order, as well as for "political stability." Evidence in favor of "public accountability" seems, however, less robust. The estimations also stress that structural reforms-such as financial development and trade openness-and human development affect private investment decisions directly, and/or through their positive impact on governance. These findings bring new empirical evidence on the subject of private investment in the developing world and in MENA countries in particular.